Model experiments of the transient response to flooding of the box shaped barge. (August 2015) - Manderbacka, Teemu; Ruponen, Pekka; Kulovesi, Jakke; Matusiak, Jerzy
Abstract: Coupling of the flooded water and ship motions was studied experimentally. Roll decay tests for one flooded compartment and transient abrupt flooding tests were performed for the box shaped barge model. The tests were conducted to obtain information on the flooding process for the development of numerical tools and to provide validation data. Quantitative values on the effect of flooded water on the roll damping were obtained. Flooded water behaves in a different manner in undivided and divided compartments. Flooded water in divided compartment increases roll damping significantly. In undivided compartment roll damping was high at low amount of flooded water. For higher amounts damping was of the same order as for the intact model. Initial flooding is a complex process where the ship and flooded water motions are coupled. Propagation of the flooding water inside the compartment, at a dam-break type abrupt flooding, was studied by tracking the surface of the flooded water. An image processing algorithm was used to obtain the tracked surface. Flooded water volume and its center of gravity were estimated from the tracked surface. Different internal layouts of the flooded compartment can lead to a totally different roll response. The inflooding jet plays an important role in the response in case of the undivided compartment. While, for a divided compartment, asymmetric flooding due to the obstructions causes high heel angle on the damage side. Abstract : Highlights: Flooded water and damaged ship dynamic interaction is studied experimentally. Origin and quantitative values of the roll damping in a damaged ship are evaluated. Kinematics of the inflooding for abrupt transient flooding is studied. Surface tracking method have been applied to estimate the inflooding.